Basalt fiber reinforced composite board in dynamic heavy load environment and preparation method thereof

By using a multi-layer structure design and a composite toughening system, the problems of weak interlayer bonding and poor impact resistance of fiber composite materials under dynamic heavy load conditions were solved, and the high strength and long service life of basalt fiber reinforced composite panels were achieved.

CN121340703AInactive Publication Date: 2026-01-16CHINA FIBER AVIATION NEW MATERIALS (CHENGDE) CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202511936523.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-22
Publication Date
2026-01-16
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing fiber composite materials exhibit weak interlayer bonding, poor impact resistance, and poor fatigue resistance under dynamic heavy load conditions, resulting in a service life that fails to meet stringent service requirements.

Method used

The design employs a multi-layer structure, including an upper surface layer, an upper reinforcing layer, a core layer, and a lower reinforcing layer. Basalt fibers are treated with processes such as plasma activation, resin matrix impregnation, and hot air curing. Combined with nanoparticles and reactive rubber, a composite toughening system is constructed, forming a continuous micro-truss interlocking structure and a stable covalent bond, achieving a seamless connection between the fiber and the resin matrix.

Benefits of technology

It improves the dynamic durability and service life of basalt fiber reinforced composite panels, enhances the impact toughness and interfacial bonding strength of the material, avoids stress concentration and corrosive media penetration, and ensures the long-term durability of the panels under dynamic loads and corrosive environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121340703A_ABST
    Figure CN121340703A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of fiber reinforced composite materials, in particular to a basalt fiber reinforced composite board in a dynamic heavy load environment and a preparation method. The basalt fiber reinforced composite board comprises an upper surface layer, an upper reinforcing layer, a core layer, a lower reinforcing layer and a lower surface layer. According to the invention, rigid nanoparticles and carboxyl-terminated nitrile rubber are introduced to construct a rigid-flexible composite toughening system, and nano aluminum oxide and silicon dioxide are taken as rigid particles and are uniformly dispersed in an epoxy cross-linked network, so that slippage and crack propagation of molecular chains can be effectively hindered, and the rigidity and damage resistance of a matrix are improved; meanwhile, the carboxyl-terminated nitrile rubber is used as reactive liquid rubber, after carboxyl of the carboxyl-terminated nitrile rubber reacts with epoxy groups, the carboxyl-terminated nitrile rubber is distributed in a matrix in a sea-island structure and can serve as stress concentration points, a large amount of crazing and shear bands can be induced, and a large amount of impact energy can be consumed; and the impact toughness is greatly improved while the high strength of the material is maintained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of fiber-reinforced composite materials technology, specifically to basalt fiber-reinforced composite panels for dynamic heavy-load environments and their preparation methods. Background Technology

[0002] With the development of modern logistics and transportation, higher demands are being placed on the lightweight, durability, and operational efficiency of transport equipment. Currently, the main structural materials for heavy-duty train carriages, containers, and freight cars are still steel (such as weathering steel) and aluminum alloys. Basalt fiber, an inorganic fiber made from melted natural basalt ore, has higher strength than glass fiber, excellent temperature resistance and acid and alkali corrosion resistance, and its cost is between that of glass fiber and carbon fiber, making it a highly promising new reinforcing material.

[0003] Existing fiber composite materials generally suffer from weak interlayer bonding and poor impact and fatigue resistance under dynamic heavy load conditions, making it difficult for them to meet the stringent service requirements.

[0004] Based on this, the present invention provides basalt fiber reinforced composite panels for dynamic heavy-load environments and their preparation method. Summary of the Invention

[0005] The purpose of this invention is to provide basalt fiber reinforced composite panels for dynamic heavy-load environments and their preparation method. The basalt fiber reinforced composite panels prepared by this invention not only have excellent static mechanical properties, but also excellent dynamic durability, effectively improving the service life of basalt fiber reinforced composite panels.

[0006] To achieve the above objectives, the present invention provides the following technical solution: a basalt fiber reinforced composite board for dynamic heavy-load environments, comprising an upper surface layer, an upper reinforcing layer, a core layer, a lower reinforcing layer, and a lower surface layer; The upper and lower surface layers have the same structure, both composed of ultrafine basalt fiber surface felt and chopped basalt fiber felt stacked together. The chopped basalt fiber felt is subjected to plasma activation treatment and resin matrix impregnation treatment. The core layer is composed of polyethylene terephthalate foam, which is impregnated with vacuum filler and surface-forming before being laid. The upper and lower reinforcing layers have the same structure, both being densely laid with unidirectional basalt fiber roving. Before being laid, the unidirectional basalt fiber roving undergoes plasma activation, treatment liquid impregnation, and hot air curing.

[0007] Preferably, the plasma activation step of the unidirectional basalt fiber roving is as follows: the unidirectional basalt fiber roving is placed in a mixed atmosphere of oxygen and argon, with a controlled power of 300-500W, a chamber pressure of 30-50Pa, and a processing time of 2-4 minutes to complete the plasma activation treatment. The treatment solution impregnation step of the unidirectional basalt fiber roving is as follows: the unidirectional basalt fiber roving is continuously passed through an impregnation tank containing treatment solution at a speed of 0.6-0.8 m / min, which is equipped with a rolling impregnation roller and a pressing roller. The rotation speed of the rolling impregnation roller is 35-40 r / min, and the pressure of the pressing roller is 0.15-0.2 MPa, thus completing the treatment solution impregnation. The hot air curing step of the unidirectional basalt fiber roving is as follows: the coated unidirectional basalt fiber roving is fed into the hot air curing channel at a speed of 0.6-0.8 m / min, with the front section at 80°C, the middle section at 90°C, and the rear section at 100°C, and the wind speed throughout the process is 1-2 m / s, to complete the hot air curing treatment.

[0008] Preferably, the treatment solution is prepared by the following method: silica micropowder and wollastonite powder are mixed at a ratio of 1-2:1, then added to a mixed solvent of silane coupling agent KH560 and ethanol solution, and activated by stirring at 35°C for 1-2 hours to obtain activated inorganic powder for later use. Nano-silica and deionized water are added to an ultrasonic disperser at a mass ratio of 1-2:50, and treated at a power of 200-300W for 15-20 minutes to obtain a nano-silica dispersion for later use. Aminated graphene and deionized water are added to... Add the graphene dispersion to the reactor and stir at 300-400 r / min for 30-40 min at 50℃ to obtain a graphene dispersion. Add the activated inorganic powder, nano silica dispersion, graphene dispersion and deionized water to a new reactor at a mass ratio of 2:8-12:0.2-0.4:65-70 and stir at 1000-1200 r / min for 30-40 min at 35℃. Then place the mixture in an ultrasonic processor and disperse it at 220W for 20-30 min to complete the preparation of the treatment solution.

[0009] Preferably, the mass ratio of the silicon micropowder, silane coupling agent KH560 and ethanol solution is 100-120:0.5-2:20, the concentration of the ethanol solution is 95%, the particle size of the silicon micropowder is 5μm, and the aspect ratio of the wollastonite powder is greater than 10.

[0010] Preferably, the polyethylene terephthalate foam undergoes a vacuum filler impregnation step before laying, which involves placing the polyethylene terephthalate foam in a vacuum impregnation area, evacuating to a vacuum level of -0.09 to -0.1 MPa and maintaining it for 20-25 minutes, introducing filler while maintaining the vacuum state and maintaining it for 15-20 minutes, breaking the vacuum and applying 0.4-0.6 MPa, holding the pressure for 30-40 minutes, and then pre-gelling at 80-90°C for 1-1.2 hours to complete the vacuum filler impregnation process. The filler is prepared as follows: Bisphenol A type epoxy resin, diluent, hollow glass microspheres and carboxyl-terminated nitrile rubber are added to a mixing container in a mass ratio of 100:8-12:10-20:5-10. After stirring at 500-800 r / min for 15-20 min at room temperature, the mixture is transferred to an ultrasonic disperser and treated at 200-300W for 10-15 min to complete the preparation of the filler. The diluent is n-butyl glycidyl ether.

[0011] Preferably, the surface construction treatment of the polyethylene terephthalate foam before laying is to use a heated embossing roller to process a continuous bidirectional dovetail groove grid on the upper and lower surfaces of the pre-gelled polyethylene terephthalate foam, with a depth of 1-2 mm, a groove width of 2-3 mm, and a groove spacing of 5-8 mm, thus completing the surface construction treatment.

[0012] Preferably, the plasma activation treatment step of the chopped basalt fiber felt is as follows: the chopped basalt fiber felt is passed through the plasma treatment zone at a speed of 1-3 m / min, a mixture of oxygen and argon with a volume ratio of 1:1 is used as the treatment gas, the power of the plasma generator is controlled at 2-5 kW, the nozzle is 10-20 mm away from the surface of the felt, and double-sided treatment is performed 1-3 times.

[0013] Preferably, the resin matrix impregnation treatment step of the upper surface layer is as follows: ultrafine basalt fiber surface felt and plasma-treated chopped basalt fiber felt are simultaneously drawn out from the felt frame, overlapped and passed through a pre-wetting tank containing resin matrix, and then the overlapped felt materials are passed through a pair of extrusion rollers to initially bond and form a composite structure, thus completing the resin matrix impregnation treatment.

[0014] Preferably, the resin matrix is ​​prepared as follows: Bisphenol A type epoxy resin is heated to 50-60°C, silane coupling agent KH560 is added, and the mixture is stirred at 200-300 r / min for 10-15 min. Then, alumina nanoparticles and silica nanoparticles are added, and the mixture is sheared and stirred at 800-1000 r / min for 20-30 min. Subsequently, a diluent and fumed silica are added, and the mixture is sheared for another 10-15 min. Then, dicyandiamide and 3-phenyl-1,1-dimethylurea are added, and the mixture is stirred for another 10- After 15 minutes, the mixture is transferred to an ultrasonic disperser and treated at 400-500W for 20-30 minutes. Finally, it is placed in a vacuum degassing machine for degassing to complete the preparation of the resin matrix. The mass ratio of the bisphenol A epoxy resin, alumina nanoparticles, silica nanoparticles, n-butyl glycidyl ether, fumed silica, silane coupling agent KH560, dicyandiamide, and 3-phenyl-1,1-dimethylurea is 100:5-10:3-5:15-25:3-5:0.5-1:3-5:0.5-1.

[0015] A method for preparing basalt fiber reinforced composite panels for dynamic heavy-load environments includes the following steps: Step 1: Take the upper and lower reinforcing layers out of the fiber yarn frame, the upper and lower surface layers out of the felt frame, and take the core layer, which has been vacuum-filled and surface-constructed, out of the material frame; Step 2: Stack the upper surface layer, upper reinforcing layer, core layer, lower reinforcing layer and lower surface layer in sequence to form a multi-layer composite structure; Step 3: Pass the multi-layer composite structure through a preheated and pre-compressed roller assembly at a traction speed of 0.3-0.6 m / min, a preheating temperature of 80-100℃, and a pre-compressing pressure of 0.2-0.3 MPa. After initial compaction, introduce it into the main forming mold with a temperature gradient. The mold temperature is controlled in segments: 120-130℃ at the inlet, 140-150℃ at the middle, and 160-170℃ at the outlet. The traction speed is 0.3-0.6 m / min to complete the curing process. Step 4: The cured multi-layer composite structure is pulled out by a continuous traction machine and cut to the set length to obtain the final basalt fiber reinforced composite board.

[0016] Compared with the prior art, the beneficial effects of the present invention are: 1. In this invention, a composite toughening system combining rigidity and flexibility is constructed by introducing rigid nanoparticles and carboxyl-terminated nitrile butadiene rubber into a multiphase system. In the resin matrix, nano-alumina and silica, as rigid particles, are uniformly dispersed in the epoxy crosslinking network, producing a significant pinning effect that effectively hinders molecular chain slippage and crack propagation, thereby improving the rigidity and damage resistance of the matrix. In the core layer, carboxyl-terminated nitrile butadiene rubber, as a reactive liquid rubber, has its carboxyl groups reacting with epoxy groups to form an island structure distributed in the matrix. When subjected to impact, it acts as a stress concentration point, inducing a large number of crazes and shear bands, consuming a large amount of impact energy. The synergistic effect of the rigid nanoparticles and carboxyl-terminated nitrile butadiene rubber particles enables the material to maintain high strength while significantly improving impact toughness.

[0017] 2. In this invention, the bidirectional dovetail grooves constructed on the surface of the polyethylene terephthalate foam core material form a continuous micro-truss interlocking structure with the panel resin, which greatly increases the interfacial bonding area and can mechanically inhibit the initiation and propagation of interfacial cracks. At the same time, the amino-graphene in the treatment liquid effectively delays the penetration of water vapor and corrosive media due to its sheet barrier effect and reactivity with epoxy resin. Nano-silica and inorganic powder activated by KH560 form a tough transition layer around the fiber, which can improve the interfacial stiffness through its rigidity and effectively buffer stress. Its stable characteristics completely avoid the risk of interfacial deterioration caused by the moisture absorption of biomass materials. With the synergy of multiple components, the long-term durability of the board is ensured under dynamic loads and corrosive environments.

[0018] 3. In this invention, a synergistic reinforcement network is constructed throughout the process by designing and chemically linking the components of the filler, the treatment liquid, and the resin matrix. The resin matrix is ​​not only a binder phase, but also forms a stable covalent bond with the activation layer composed of nano-silica, amino graphene, and activated inorganic powders constructed on the fiber surface by the treatment liquid. This achieves a seamless connection from the reinforcing fiber to the resin matrix. This strong interface efficiently transfers stress to the core layer. The epoxy component in the core layer filler is inherently compatible with the resin matrix, and the hollow glass microspheres share the in-plane load with the panel. Through full-process optimization, the load is uniformly diffused within the composite material, avoiding local stress concentration, thus jointly creating the superior tensile and bending properties of the board. Attached Figure Description

[0019] Figure 1 This is a flowchart illustrating the basalt fiber reinforced composite board for dynamic heavy-load environments and its preparation method proposed in this invention. Detailed Implementation

[0020] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0021] It should be noted that the raw materials used in the following embodiments are all commercially available raw materials; The polyethylene terephthalate foam is an AIREX T92 series product from AIREX Corporation.

[0022] Example 1: Basalt fiber reinforced composite panel for dynamic heavy-load environment, including upper surface layer, upper reinforcement layer, core layer, lower reinforcement layer and lower surface layer; The upper and lower surface layers have the same structure, both composed of ultrafine basalt fiber surface felt and chopped basalt fiber felt stacked together. The chopped basalt fiber felt is subjected to plasma activation treatment and resin matrix impregnation treatment. The plasma activation treatment steps for chopped basalt fiber felt are as follows: the chopped basalt fiber felt is passed through the plasma treatment zone at a speed of 1-3 m / min, a mixture of oxygen and argon with a volume ratio of 1:1 is used as the treatment gas, the power of the plasma generator is controlled at 2kW, the nozzle is 10mm away from the surface of the felt, and a double-sided treatment is performed once.

[0023] The resin matrix impregnation process for the upper surface layer is as follows: ultrafine basalt fiber surface felt and plasma-treated chopped basalt fiber felt are simultaneously drawn out from the felt frame, overlapped and passed through a pre-wetting tank containing resin matrix. The overlapping felts are then passed through a pair of extrusion rollers to initially bond and form a composite structure, thus completing the resin matrix impregnation process.

[0024] The resin matrix was prepared as follows: bisphenol A epoxy resin was heated to 50°C, silane coupling agent KH560 was added, and the mixture was stirred at 200 r / min for 10 min. Then, alumina nanoparticles and silica nanoparticles were added, and the mixture was sheared and stirred at 800 r / min for 20 min. Subsequently, diluent and fumed silica were added, and shearing was continued for 10-15 min. Then, dicyandiamide and 3-phenyl-1,1-dimethylurea were added, and the mixture was stirred for 10 min. The mixture was then transferred to an ultrasonic disperser and treated at 400 W for 20 min. Finally, the mixture was placed in a vacuum degassing machine for degassing treatment to complete the preparation of the resin matrix. The mass ratio of bisphenol A epoxy resin, alumina nanoparticles, silica nanoparticles, n-butyl glycidyl ether, fumed silica, silane coupling agent KH560, dicyandiamide, and 3-phenyl-1,1-dimethylurea was 100:5:3:15:3:0.5:3:0.5.

[0025] The core layer is composed of polyethylene terephthalate foam, which is impregnated with vacuum filler and surface-forming before being laid. Before laying, polyethylene terephthalate foam undergoes a vacuum filler impregnation process as follows: the polyethylene terephthalate foam is placed in a vacuum impregnation area, a vacuum of -0.09 MPa is drawn and maintained for 20 minutes, filler is introduced while maintaining the vacuum state and maintained for 15 minutes, the vacuum is broken and 0.4 MPa is applied, pressure is maintained for 30 minutes, and then pre-gelled at 80℃ for 1 hour to complete the vacuum filler impregnation process. The filler is prepared as follows: Bisphenol A type epoxy resin, diluent, hollow glass microspheres and carboxyl-terminated butadiene nitrile rubber are added to a mixing container in a mass ratio of 100:8:10:5. After stirring at 500 r / min for 15 min at room temperature, the mixture is transferred to an ultrasonic disperser and treated at 200 W for 10 min to complete the preparation of the filler. The diluent is n-butyl glycidyl ether.

[0026] The surface preparation of polyethylene terephthalate foam before laying is to use a heated embossing roller to process a continuous bidirectional dovetail groove grid on the upper and lower surfaces of the pre-gelled polyethylene terephthalate foam. The groove grid has a depth of 1 mm, a width of 2 mm, and a spacing of 5 mm, thus completing the surface preparation.

[0027] The upper and lower reinforcing layers have the same structure, both consisting of densely laid unidirectional basalt fiber rovings. Before being laid, the unidirectional basalt fiber rovings undergo plasma activation, impregnation with a treatment solution, and hot air curing.

[0028] The plasma activation steps for unidirectional basalt fiber roving are as follows: the unidirectional basalt fiber roving is placed in a mixed atmosphere of oxygen and argon, with a power of 300W, a chamber pressure of 30Pa, and a treatment time of 2min to complete the plasma activation treatment. The treatment solution impregnation process for unidirectional basalt fiber roving is as follows: the unidirectional basalt fiber roving is continuously passed through an impregnation tank containing treatment solution at a speed of 0.6 m / min, which is equipped with a rolling impregnation roller and a pressing roller. The rotation speed of the rolling impregnation roller is 35 r / min, and the pressure of the pressing roller is 0.15 MPa, thus completing the treatment solution impregnation process. The hot air curing process for unidirectional basalt fiber roving is as follows: the coated unidirectional basalt fiber roving is fed into the hot air curing channel at a speed of 0.6 m / min, with the temperature at 80°C in the first section, 90°C in the middle section, and 100°C in the last section, and the wind speed at 1 m / s throughout the process, thus completing the hot air curing treatment.

[0029] The treatment solution was prepared by the following method: Silica powder and wollastonite powder were mixed at a ratio of 1-2:1, and then added to a mixed solvent of silane coupling agent KH560 and ethanol solution. The mixture was stirred and activated at 35°C for 1 hour to obtain activated inorganic powder, which was then set aside. Nano-silica and deionized water were added to an ultrasonic disperser at a mass ratio of 1:50 and treated at 200W for 15 minutes to obtain a nano-silica dispersion, which was then set aside. Aminated graphene and deionized water were added to a reaction vessel at a mass ratio of 1:50 and stirred at 300r / min for 30 minutes at 50°C to obtain a graphene dispersion. The activated inorganic powder, nano-silica dispersion, graphene dispersion, and deionized water were added to a new reaction vessel at a mass ratio of 2:8:0.2:65 and stirred at 1000r / min for 30 minutes at 35°C. The mixture was then placed in an ultrasonic processor and dispersed at 220W for 20 minutes to complete the preparation of the treatment solution.

[0030] The mass ratio of silica powder, silane coupling agent KH560 and ethanol solution is 100:0.5:20, the concentration of ethanol solution is 95%, the particle size of silica powder is 5μm, and the aspect ratio of wollastonite powder is greater than 10.

[0031] A method for preparing basalt fiber reinforced composite panels for dynamic heavy-load environments includes the following steps: Step 1: Take the upper and lower reinforcing layers out of the fiber yarn frame, the upper and lower surface layers out of the felt frame, and take the core layer, which has been vacuum-filled and surface-constructed, out of the material frame; Step 2: Stack the upper surface layer, upper reinforcing layer, core layer, lower reinforcing layer and lower surface layer in sequence to form a multi-layer composite structure; Step 3: The multi-layer composite structure is passed through a preheated and pre-compressed roller group at a traction speed of 0.3 m / min, a preheating temperature of 80℃, and a pre-compressing pressure of 0.2 MPa. After initial compaction, it is introduced into the main forming mold with a temperature gradient. The mold temperature is controlled in sections: 120℃ at the inlet, 140℃ in the middle, and 160℃ at the outlet. The traction speed is 0.3 m / min to complete the curing process. Step 4: The cured multi-layer composite structure is pulled out by a continuous traction machine and cut to the set length to obtain the final basalt fiber reinforced composite board.

[0032] Example 2: Basalt fiber reinforced composite panel for dynamic heavy-load environment, including upper surface layer, upper reinforcing layer, core layer, lower reinforcing layer and lower surface layer; The upper and lower surface layers have the same structure, both composed of ultrafine basalt fiber surface felt and chopped basalt fiber felt stacked together. The chopped basalt fiber felt is subjected to plasma activation treatment and resin matrix impregnation treatment. The plasma activation treatment steps for chopped basalt fiber felt are as follows: the chopped basalt fiber felt is passed through the plasma treatment zone at a speed of 2 m / min, a mixture of oxygen and argon with a volume ratio of 1:1 is used as the treatment gas, the power of the plasma generator is controlled at 3kW, the nozzle is 15mm away from the surface of the felt, and double-sided treatment is performed twice.

[0033] The resin matrix impregnation process for the upper surface layer is as follows: ultrafine basalt fiber surface felt and plasma-treated chopped basalt fiber felt are simultaneously drawn out from the felt frame, overlapped and passed through a pre-wetting tank containing resin matrix. The overlapping felts are then passed through a pair of extrusion rollers to initially bond and form a composite structure, thus completing the resin matrix impregnation process.

[0034] The resin matrix was prepared as follows: bisphenol A epoxy resin was heated to 55°C, silane coupling agent KH560 was added, and the mixture was stirred at 250 r / min for 12 min. Then, alumina nanoparticles and silica nanoparticles were added, and the mixture was sheared and stirred at 900 r / min for 25 min. Subsequently, diluent and fumed silica were added, and the mixture was sheared for another 13 min. Then, dicyandiamide and 3-phenyl-1,1-dimethylurea were added, and the mixture was stirred for another 13 min. The mixture was then transferred to an ultrasonic disperser and treated at 450 W for 25 min. Finally, the mixture was placed in a vacuum degassing machine for degassing treatment to complete the preparation of the resin matrix. The mass ratio of bisphenol A epoxy resin, alumina nanoparticles, silica nanoparticles, n-butyl glycidyl ether, fumed silica, silane coupling agent KH560, dicyandiamide, and 3-phenyl-1,1-dimethylurea was 100:7:4:20:4:0.72:4:0.7.

[0035] The core layer is composed of polyethylene terephthalate foam, which is impregnated with vacuum filler and surface-forming before being laid. Before laying, polyethylene terephthalate foam undergoes a vacuum filler impregnation process as follows: the polyethylene terephthalate foam is placed in a vacuum impregnation area, a vacuum of -0.09 MPa is drawn and maintained for 22 minutes, filler is introduced while maintaining the vacuum state and maintained for 18 minutes, the vacuum is broken and 0.5 MPa is applied, pressure is maintained for 35 minutes, and then pre-gelled at 85℃ for 1.1 hours to complete the vacuum filler impregnation process. The filler is prepared as follows: Bisphenol A type epoxy resin, diluent, hollow glass microspheres and carboxyl-terminated nitrile rubber are added to a mixing container in a mass ratio of 100:10:15:7.5. After stirring at 600 r / min for 17 min at room temperature, the mixture is transferred to an ultrasonic disperser and treated at 250 W for 12 min to complete the preparation of the filler. The diluent is n-butyl glycidyl ether.

[0036] The surface preparation of polyethylene terephthalate foam before laying is to use a heated embossing roller to process a continuous bidirectional dovetail groove grid on the upper and lower surfaces of the pre-gelled polyethylene terephthalate foam. The groove grid has a depth of 1 mm, a width of 2 mm, and a spacing of 6 mm, thus completing the surface preparation.

[0037] The upper and lower reinforcing layers have the same structure, both consisting of densely laid unidirectional basalt fiber rovings. Before being laid, the unidirectional basalt fiber rovings undergo plasma activation, impregnation with a treatment solution, and hot air curing.

[0038] The plasma activation steps for unidirectional basalt fiber roving are as follows: the unidirectional basalt fiber roving is placed in a mixed atmosphere of oxygen and argon, with a power of 400W, a chamber pressure of 40Pa, and a treatment time of 3min to complete the plasma activation treatment. The treatment solution impregnation process for unidirectional basalt fiber roving is as follows: the unidirectional basalt fiber roving is continuously passed through an impregnation tank containing treatment solution at a speed of 0.7 m / min, which is equipped with a rolling impregnation roller and a pressing roller. The rotation speed of the rolling impregnation roller is 37 r / min, and the pressure of the pressing roller is 0.17 MPa, thus completing the treatment solution impregnation process. The hot air curing process for unidirectional basalt fiber roving is as follows: the coated unidirectional basalt fiber roving is fed into the hot air curing channel at a speed of 0.7 m / min, with the temperature at 80°C in the first section, 90°C in the middle section, and 100°C in the last section, and the wind speed throughout is 1.5 m / s, thus completing the hot air curing treatment.

[0039] The treatment solution was prepared by the following method: Silica micropowder and wollastonite powder were mixed at a ratio of 1-2:1, and then added to a mixed solvent of silane coupling agent KH560 and ethanol solution. The mixture was stirred and activated at 35°C for 1.5 hours to obtain activated inorganic powder, which was then set aside. Nano-silica and deionized water were added to an ultrasonic disperser at a mass ratio of 1.5:50 and treated at 250W for 17 minutes to obtain a nano-silica dispersion, which was then set aside. Aminated graphene and deionized water were then added according to a mass ratio... 1.5:50 were added to the reactor, and the mixture was stirred at 350 r / min for 35 min at 50 °C to obtain a graphene dispersion. The activated inorganic powder, nano silica dispersion, graphene dispersion and deionized water were added to a new reactor at a mass ratio of 2:10:0.3:67. The mixture was stirred at 1100 r / min for 35 min at 35 °C. Then it was placed in an ultrasonic processor and dispersed at 220 W for 25 min to complete the preparation of the treatment solution.

[0040] The mass ratio of silica powder, silane coupling agent KH560 and ethanol solution is 110:1:20, the concentration of ethanol solution is 95%, the particle size of silica powder is 5μm, and the aspect ratio of wollastonite powder is greater than 10.

[0041] A method for preparing basalt fiber reinforced composite panels for dynamic heavy-load environments includes the following steps: Step 1: Take the upper and lower reinforcing layers out of the fiber yarn frame, the upper and lower surface layers out of the felt frame, and take the core layer, which has been vacuum-filled and surface-constructed, out of the material frame; Step 2: Stack the upper surface layer, upper reinforcing layer, core layer, lower reinforcing layer and lower surface layer in sequence to form a multi-layer composite structure; Step 3: The multi-layer composite structure is passed through a preheated and pre-pressed roller group at a traction speed of 0.4 m / min, a preheating temperature of 90℃, and a pre-pressing pressure of 0.3 MPa. After initial compaction, it is introduced into the main forming mold with a temperature gradient. The mold temperature is controlled in sections: 125℃ at the inlet, 145℃ in the middle, and 165℃ at the outlet. The traction speed is 0.4 m / min to complete the curing process. Step 4: The cured multi-layer composite structure is pulled out by a continuous traction machine and cut to the set length to obtain the final basalt fiber reinforced composite board.

[0042] Example 3: Basalt fiber reinforced composite panel for dynamic heavy-load environment, including upper surface layer, upper reinforcement layer, core layer, lower reinforcement layer and lower surface layer; The upper and lower surface layers have the same structure, both composed of ultrafine basalt fiber surface felt and chopped basalt fiber felt stacked together. The chopped basalt fiber felt is subjected to plasma activation treatment and resin matrix impregnation treatment. The plasma activation treatment steps for chopped basalt fiber felt are as follows: the chopped basalt fiber felt is passed through the plasma treatment zone at a speed of 3 m / min, a mixture of oxygen and argon with a volume ratio of 1:1 is used as the treatment gas, the power of the plasma generator is controlled at 5 kW, the nozzle is 20 mm away from the surface of the felt, and double-sided treatment is performed 3 times.

[0043] The resin matrix impregnation process for the upper surface layer is as follows: ultrafine basalt fiber surface felt and plasma-treated chopped basalt fiber felt are simultaneously drawn out from the felt frame, overlapped and passed through a pre-wetting tank containing resin matrix. The overlapping felts are then passed through a pair of extrusion rollers to initially bond and form a composite structure, thus completing the resin matrix impregnation process.

[0044] The resin matrix was prepared as follows: bisphenol A epoxy resin was heated to 60°C, silane coupling agent KH560 was added, and the mixture was stirred at 300 r / min for 15 min. Then, alumina nanoparticles and silica nanoparticles were added, and the mixture was sheared and stirred at 1000 r / min for 30 min. Subsequently, diluent and fumed silica were added, and the mixture was sheared for another 15 min. Then, dicyandiamide and 3-phenyl-1,1-dimethylurea were added, and the mixture was stirred for another 15 min. The mixture was then transferred to an ultrasonic disperser and treated at 500 W for 30 min. Finally, the mixture was placed in a vacuum degassing machine for degassing treatment to complete the preparation of the resin matrix. The mass ratio of bisphenol A epoxy resin, alumina nanoparticles, silica nanoparticles, n-butyl glycidyl ether, fumed silica, silane coupling agent KH560, dicyandiamide, and 3-phenyl-1,1-dimethylurea was 100:10:5:25:5:1:5:1.

[0045] The core layer is composed of polyethylene terephthalate foam, which is impregnated with vacuum filler and surface-forming before being laid. Before laying, polyethylene terephthalate foam undergoes a vacuum filler impregnation process as follows: the polyethylene terephthalate foam is placed in a vacuum impregnation area, a vacuum of -0.1 MPa is maintained for 25 minutes, filler is introduced while maintaining the vacuum state and maintained for 20 minutes, the vacuum is broken and 0.6 MPa is applied, pressure is maintained for 40 minutes, and then pre-gelled at 90℃ for 1.2 hours to complete the vacuum filler impregnation process. The filler is prepared as follows: Bisphenol A type epoxy resin, diluent, hollow glass microspheres and carboxyl-terminated butadiene nitrile rubber are added to a mixing container in a mass ratio of 100:12:20:10. After stirring at 800 r / min for 20 min at room temperature, the mixture is transferred to an ultrasonic disperser and treated at 300 W for 15 min to complete the preparation of the filler. The diluent is n-butyl glycidyl ether.

[0046] The surface preparation of polyethylene terephthalate foam before laying is to use a heated embossing roller to process a continuous bidirectional dovetail groove grid on the upper and lower surfaces of the pre-gelled polyethylene terephthalate foam. The groove grid has a depth of 2mm, a width of 3mm, and a spacing of 8mm, thus completing the surface preparation.

[0047] The upper and lower reinforcing layers have the same structure, both consisting of densely laid unidirectional basalt fiber rovings. Before being laid, the unidirectional basalt fiber rovings undergo plasma activation, impregnation with a treatment solution, and hot air curing.

[0048] The plasma activation steps for unidirectional basalt fiber roving are as follows: the unidirectional basalt fiber roving is placed in a mixed atmosphere of oxygen and argon, with a power of 500W, a chamber pressure of 50Pa, and a treatment time of 4min to complete the plasma activation treatment. The treatment solution impregnation process for unidirectional basalt fiber roving is as follows: the unidirectional basalt fiber roving is continuously passed through an impregnation tank containing treatment solution at a speed of 0.8 m / min, which is equipped with a rolling impregnation roller and a pressing roller. The rotation speed of the rolling impregnation roller is 40 r / min, and the pressure of the pressing roller is 0.2 MPa, thus completing the treatment solution impregnation process. The hot air curing process for unidirectional basalt fiber roving is as follows: the coated unidirectional basalt fiber roving is fed into the hot air curing channel at a speed of 0.8 m / min, with the temperature at 80°C in the first section, 90°C in the middle section, and 100°C in the last section, and the wind speed at 2 m / s throughout the process, thus completing the hot air curing treatment.

[0049] The treatment solution was prepared by the following method: Silica micropowder and wollastonite powder were mixed at a ratio of 1-2:1, and then added to a mixed solvent of silane coupling agent KH560 and ethanol solution. The mixture was stirred and activated at 35°C for 2 hours to obtain activated inorganic powder for later use. Nano-silica and deionized water were added to an ultrasonic disperser at a mass ratio of 2:50 and treated at 300W for 20 minutes to obtain a nano-silica dispersion for later use. Aminated graphene and deionized water were then added at a mass ratio of 2:50... The mixture was added to a reaction vessel and stirred at 300-400 r / min for 30-40 min at 50℃ to obtain a graphene dispersion. The activated inorganic powder, nano silica dispersion, graphene dispersion and deionized water were added to a new reaction vessel at a mass ratio of 2:12:0.4:70 and stirred at 1200 r / min for 40 min at 35℃. Then the mixture was placed in an ultrasonic processor and dispersed at 220 W for 30 min to complete the preparation of the treatment solution.

[0050] The mass ratio of silica powder, silane coupling agent KH560 and ethanol solution is 120:2:20, the concentration of ethanol solution is 95%, the particle size of silica powder is 5μm, and the aspect ratio of wollastonite powder is greater than 10.

[0051] A method for preparing basalt fiber reinforced composite panels for dynamic heavy-load environments includes the following steps: Step 1: Take the upper and lower reinforcing layers out of the fiber yarn frame, the upper and lower surface layers out of the felt frame, and take the core layer, which has been vacuum-filled and surface-constructed, out of the material frame; Step 2: Stack the upper surface layer, upper reinforcing layer, core layer, lower reinforcing layer and lower surface layer in sequence to form a multi-layer composite structure; Step 3: The multi-layer composite structure is passed through a preheated and pre-compressed roller group at a traction speed of 0.6 m / min, a preheating temperature of 100℃, and a pre-compressing pressure of 0.3 MPa. After initial compaction, it is introduced into the main forming mold with a temperature gradient. The mold temperature is controlled in sections: 130℃ at the inlet, 150℃ in the middle, and 170℃ at the outlet. The traction speed is 0.6 m / min to complete the curing process. Step 4: The cured multi-layer composite structure is pulled out by a continuous traction machine and cut to the set length to obtain the final basalt fiber reinforced composite board.

[0052] Comparative Example 1 differs from Example 1 in that the upper and lower surface layers were not impregnated with resin matrix in this comparative example, and the resin matrix was replaced with a single bisphenol A type epoxy resin.

[0053] Comparative Example 2 differs from Example 1 in that the core layer was not vacuum impregnated and the filler was replaced with a single bisphenol A type epoxy resin.

[0054] Comparative Example 3 differs from Example 1 in that the upper and lower reinforcing layers were not dipped in the treatment solution in this comparative example, but instead a single bisphenol A type epoxy resin was used.

[0055] Performance testing: Performance tests were conducted on the basalt fiber reinforced composite panels prepared in Examples 1-3 and Comparative Examples 1-3, including: Tensile strength test: Refer to the national standard GB / T1447-2005 "Test method for tensile properties of fiber reinforced plastics", use a universal testing machine, the sample size refers to the standard specification (usually 250mm×25mm×thickness), the tensile speed is controlled at 2mm / min, and the maximum tensile stress (MPa) is recorded. Elastic modulus test: The elastic modulus is calculated using the linear part of the stress-strain curve, referring to the national standard GB / T1447-2005. Impact resistance test: GB / T1843-2008 "Determination of impact strength of plastic cantilever beam", using a cantilever beam impact testing machine, sample size 80mm×10mm×4mm, standard notch prepared, and impact strength measured (kJ / m). 2 ); Fatigue resistance test: GB / T16779-2008 "Test method for fatigue properties of fiber reinforced plastic laminate", the method is tensile-tensile fatigue, stress ratio R=0.1, frequency 5Hz, and the number of failure cycles is recorded; Corrosion resistance test: Following standard ASTM B117, samples were exposed to 5% NaCl salt spray at 35°C for 500 hours. Tensile strength was then measured, and the strength retention rate (%) was calculated, which is the ratio of the tensile strength after corrosion to the initial tensile strength. The test data are recorded in Table 1 below: Table 1 Performance Test Table for Basalt Fiber Reinforced Composite Boards

[0056] As shown in Table 1, in Examples 1-3, plasma activation introduces active functional groups onto the fiber surface, which synergistically construct a robust covalent bond interface with the silane coupling agent, greatly improving load transfer efficiency. Alumina and silica nanoparticles in the resin matrix act as rigid fillers, generating a pinning effect in the crosslinked network, significantly enhancing rigidity, toughness, and impact resistance. The core layer, through vacuum impregnation of fillers and the construction of dovetail groove microstructures on the surface, achieves elastic toughening and mechanical interlocking, synergistically improving impact and fatigue resistance. The reinforcing layer is constructed using silica powder and wollastonite powder. The treatment liquid composed of nano-silica and graphene is functionalized to form a strong and dense transition layer. After activation by KH560, the silica powder and wollastonite powder form a strong chemical bond and mechanical interlock with the fiber and resin. This not only forms a reinforcing layer around the fiber that can effectively transfer stress and improve the interface stiffness, but its inherent hydrophobicity and chemical stability, together with nano-silica and amino graphene, also construct a multi-level protective interface with reinforcement, toughening and barrier functions, thus contributing to excellent fatigue durability and corrosion resistance. In Comparative Example 1, the surface layer was not reinforced with resin, using only epoxy resin. The lack of the pinning toughening effect of nanoparticles and the bridging effect of silane coupling agents resulted in a fragile fiber-resin interface, leading to ineffective load transfer and reduced tensile strength and corrosion resistance. In Comparative Example 2, the core layer lacked filler; the bonding between the pure polyethylene terephthalate foam and the panel relied solely on surface physical adhesion. Furthermore, the foam itself had low modulus and toughness, making it prone to delamination under impact and cyclic loading, and the core material easily crushed, resulting in a sharp decline in impact resistance and fatigue performance. In Comparative Example 3, the reinforcing layer treatment solution was not used; the single epoxy resin treatment solution resulted in a brittle interface layer lacking the rigid reinforcement effect of silica powder, wollastonite powder, and nano-silica, as well as the sheet barrier effect of aminated graphene. Under dynamic loading, microcracks at this fragile interface rapidly propagated, significantly shortening fatigue life. Simultaneously, corrosive media more easily penetrated along the interface, and the lack of a chemically stable barrier provided by inorganic silicate fillers further reduced corrosion resistance.

[0057] By comparing and analyzing the relevant data in the table, it can be seen that the basalt fiber reinforced composite board prepared by the present invention not only has excellent static mechanical properties, but also excellent dynamic durability properties, effectively improving the service life of the basalt fiber reinforced composite board.

[0058] In the description of this specification, references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.

[0059] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to the specific implementations described. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention. The invention is limited only by the claims and their full scope and equivalents.

Claims

1. Basalt fiber reinforced composite panel for dynamic overloading environment, characterized in that: The upper surface layer, the upper reinforcing layer, the core layer, the lower reinforcing layer and the lower surface layer are provided. The upper surface layer and the lower surface layer are identical in structure and are composed of a superfine basalt fiber surface felt and a chopped basalt fiber felt, and the chopped basalt fiber felt is subjected to plasma activation treatment and resin matrix infiltration treatment. The core layer is composed of polyethylene terephthalate foam, and the polyethylene terephthalate foam is subjected to vacuum filler impregnation and surface construction treatment before laying. The upper reinforcing layer and the lower reinforcing layer are identical in structure and are composed of densely laid unidirectional basalt fiber roving, and the unidirectional basalt fiber roving is subjected to plasma activation, treatment liquid immersion coating and hot air curing before laying.

2. The basalt fiber reinforced composite panel for dynamic load environment according to claim 1, characterized in that, The plasma activation step of the unidirectional basalt fiber roving is that the unidirectional basalt fiber roving is subjected to plasma activation treatment in a mixed gas atmosphere of oxygen and argon, with a power of 300-500W, a chamber pressure of 30-50Pa and a treatment time of 2-4min. The treatment liquid immersion coating step of the unidirectional basalt fiber roving is that the unidirectional basalt fiber roving is continuously passed through a wetting tank containing a treatment liquid and provided with a rolling immersion coating roller and an extrusion roller at a speed of 0.6-0.8m / min, the rolling immersion coating roller rotates at a speed of 35-40r / min, and the extrusion roller has a pressure of 0.15-0.2MPa. The hot air curing step of the unidirectional basalt fiber roving is that the immersed unidirectional basalt fiber roving is sent into a hot air curing channel at a speed of 0.6-0.8m / min, with a front section of 80℃, a middle section of 90℃ and a rear section of 100℃, and a wind speed of 1-2m / s throughout the channel.

3. The basalt fiber reinforced composite panel for dynamic load environment according to claim 2, characterized in that, The treatment liquid is prepared by the following method: mixing silicon powder and wollastonite powder at a ratio of 1-2:1, adding a mixed solvent of silane coupling agent KH560 and ethanol solution, stirring and activating at 35℃ for 1-2h to obtain activated inorganic powder, adding nano-silicon dioxide and deionized water into an ultrasonic disperser at a mass ratio of 1-2:50, treating at a power of 200-300W for 15-20min to obtain a nano-silicon dioxide dispersion liquid, adding amino-graphene and deionized water into a reaction kettle at a mass ratio of 1-2:50, stirring at 300-400r / min at 50℃ for 30-40min to obtain a graphene dispersion liquid, adding the activated inorganic powder, the nano-silicon dioxide dispersion liquid, the graphene dispersion liquid and deionized water into a new reaction kettle at a mass ratio of 2:8-12:0.2-0.4:65-70, stirring at 1000-1200r / min at 35℃ for 30-40min, and then dispersing in an ultrasonic treatment machine at 220W for 20-30min to complete the preparation of the treatment liquid.

4. The basalt fiber reinforced composite panel for dynamic load environment according to claim 3, characterized in that, The mass ratio of the silicon powder, the silane coupling agent KH560 and the ethanol solution is 100-120:0.5-2:20, the concentration of the ethanol solution is 95%, the particle size of the silicon powder is 5μm, and the aspect ratio of the wollastonite powder is greater than 10.

5. The basalt fiber reinforced composite panel for dynamic load environment according to claim 4, characterized in that, The polyethylene terephthalate foam is subjected to a vacuum filler impregnation step before laying, the polyethylene terephthalate foam is placed in a vacuum impregnation area, vacuum is extracted to keep for 20-25 min under a vacuum degree of -0.09 to -0.1 MPa, filler is introduced under the vacuum state, and kept for 15-20 min, after the vacuum is broken, 0.4-0.6 MPa is applied, and after pressure maintaining for 30-40 min, pre-gel treatment is carried out at 80-90℃ for 1-1.2 h, and the vacuum filler impregnation treatment is completed; The preparation method of the filler is that bisphenol A type epoxy resin, diluent, hollow glass microbeads and carboxyl-terminated butylnitrile rubber are added into a mixing container according to a mass ratio of 100:8-12:10-20:5-10, stirring is carried out at 500-800 r / min at room temperature for 15-20 min, then the mixture is transferred to an ultrasonic disperser, and treated at 200-300 W for 10-15 min, and the preparation of the filler is completed; The diluent is n-butyl glycidyl ether.

6. The basalt fiber reinforced composite panel for dynamic load environment according to claim 5, characterized in that, The surface construction treatment of the polyethylene terephthalate foam before laying is that a heated embossing roller is used to process continuous bidirectional dovetail groove grids on the upper and lower surfaces of the pre-gel treated polyethylene terephthalate foam, the depth is 1-2 mm, the groove width is 2-3 mm, and the groove spacing is 5-8 mm, and the surface construction treatment is completed.

7. The basalt fiber reinforced composite panel for dynamic load environment according to claim 6, characterized in that, The plasma activation treatment step of the chopped basalt fiber mat is that the chopped basalt fiber mat is passed through a plasma treatment area at a speed of 1-3 m / min, a mixed gas of oxygen and argon in a volume ratio of 1:1 is used as the treatment gas, the power of the plasma generator is controlled to be 2-5 kW, the nozzle is 10-20 mm away from the surface of the mat material, and double-sided treatment is carried out for 1-3 times.

8. The basalt fiber reinforced composite panel for dynamic load environment according to claim 7, characterized in that, The resin matrix infiltration treatment step of the upper surface layer is that superfine basalt fiber surface mat and the chopped basalt fiber mat subjected to plasma treatment are simultaneously drawn out from the mat rack, the two are overlapped and passed through a pre-wetting tank containing the resin matrix, and then the overlapped mat material is passed through a pair of extrusion rollers to preliminarily bond to form a composite structure, and the resin matrix infiltration treatment is completed.

9. The basalt fiber reinforced composite panel for dynamic load environment according to claim 8, characterized in that, The preparation method of the resin matrix is as follows: the bisphenol A type epoxy resin is heated to 50-60 DEG C, the silane coupling agent KH560 is added, stirring at 200-300 r / min for 10-15 min, then the alumina nanoparticles and the silicon dioxide nanoparticles are added, high-speed shearing stirring at 800-1000 r / min for 20-30 min, then the diluent and the fumed silica are added, continuing shearing for 10-15 min, then the dicyandiamide and the 3-phenyl-1,1-dimethylurea are added, continuing stirring for 10-15 min, transferring to an ultrasonic disperser, treating at 400-500 W for 20-30 min, finally placing in a vacuum defoaming machine for defoaming treatment, completing the preparation of the resin matrix, and the mass ratio of the bisphenol A type epoxy resin, the alumina nanoparticles, the silicon dioxide nanoparticles, the n-butyl glycidyl ether, the fumed silica, the silane coupling agent KH560, the dicyandiamide and the 3-phenyl-1,1-dimethylurea is 100:5-10:3-5:15-25:3-5:0.5-1:3-5:0.5-1.

10. A method of producing a basalt fiber reinforced composite panel for dynamic heavy load environment according to any one of claims 1 to 9, characterized in that, The method comprises the following steps: Step one: the upper and lower reinforcement layers are drawn out from the fiber yarn frame, the upper and lower surface layers are drawn out from the felt frame, and the core layer subjected to vacuum filler impregnation and surface construction treatment is drawn out from the material frame; Step two: the upper surface layer, the upper reinforcement layer, the core layer, the lower reinforcement layer and the lower surface layer are sequentially laminated to form a multi-layer composite structure; Step three: the multi-layer composite structure is drawn through a preheating and pre-pressing roller group, the drawing speed is 0.3-0.6 m / min, the preheating temperature is 80-100 DEG C, the pre-pressing pressure is 0.2-0.3 MPa, after preliminary compaction, the multi-layer composite structure is introduced into a main forming mold with a temperature gradient, the mold temperature is controlled in sections as 120-130 DEG C for the inlet section, 140-150 DEG C for the middle section and 160-170 DEG C for the outlet section, the drawing speed is 0.3-0.6 m / min, and the curing treatment is completed; Step four: the multi-layer composite structure subjected to the curing treatment is drawn out through a continuous drawing machine, and is cut according to the set length, so that the final basalt fiber reinforced composite plate is obtained.

Citation Information

Cited By

  • Compression-resistant PET plastic bottle composite material and preparation method thereof

    CN121991474A